The right of communication to the public in EU copyright law - Koo, Justin (Oxford, UK ; Portland, Oregon : Hart Publishing, 2019)
"This monograph conducts a comprehensive analysis of the EU right of communication to the public, one of the exclusive rights under EU copyright law, and provides an alternative framework for its interpretation and application. The present state of the law is unsatisfactory; there is uncertainty in the acquis communautaire and courts at the EU and domestic levels have struggled to apply the right. Therefore, the book identifies the problems with the existing right of communication to the public and proposes recommendations for reform. In addition to reforming the scope of the right of communication to the public, the jurisdiction and applicable law in relation to the right are analysed and changes are recommended. Thus, the book covers both the scope and practicalities of a coherent and effective reform of the right. In light of the continuing development and accompanying tribulations with this right at the EU level, this book provides a topical and timely analysis that will be of interest to academics and practitioners working on EU copyright law."--Bloomsbury Publishing.
I. Subject-Matter -- II. Significance and Contribution -- III. Structure -- IV. Scope -- 1. Justifying EU Copyright Law: Constructing a Normative Framework for the Right of Communication to the Public -- I. Introduction -- II. Constructing a Normative Framework for the EU Right of Communication to the Public -- III. Proportionality -- IV. Certainty -- V. Conclusion - Developing the EU Right of Communication to the Public -- 2. Journey from Rafael Hoteles to Renckhoff : Exploring the EU Right of Communication to the Public -- I. Introduction -- II. Making Sense of the EU Communication to the Public Right -- III. Understanding the Legal Reasoning of the CJEU in the Communication to the Public Cases -- IV. Conclusion -- 3. The Problems with the Right of Communication to the Public -- I. Introduction -- II. Broad Interpretation -- III. 'Communication' -- IV. The Making Available Aspect -- V. Reception in Public -- VI. 'New Public' -- VII. 'Knowledge' and 'for Profit' -- VIII. Conclusion -- 4. Structuring the Reformed Right of Communication to the Public Under EU Copyright Law -- I. Introduction -- II. The Reformed Right of Communication to the Public -- III. Reconciling the Reformed Right with the Existing Copyright Framework -- IV. Completing the Harmonisation of the Communication to the Public Right -- V. Conclusion -- 5. Locating and Establishing Responsibility for the Act of Communication to the Public -- I. Introduction -- II. Where Does the Act of Communication to the Public Occur? -- III. Conclusion -- 6. Enforcing the Reformed Right of Communication to the Public: Choice of Jurisdiction -- I. Introduction -- II. Establishing Jurisdiction in EU Copyright Cases - The Current Approach -- III. Establishing Jurisdiction for the Reformed Communication to the Public Right -- IV. Conclusion -- 7. Enforcing the Reformed Right of Communication to the Public: Choice of Applicable Law -- I. Introduction -- II. Establishing Applicable Law in EU Copyright Cases - The Current Approach -- III. Establishing Applicable Law for the Reformed Communication to the Public Right -- IV. Conclusion -- 8. Applying the Reformed Right of Communication to the Public: Case Studies -- I. Introduction -- II. Rafael Hoteles - Acts of Cable Retransmission -- III. FAPL v QC Leisure - Acts of Reception in Public -- IV. ITV v TVCatchup - Acts of Internet Retransmission ('Simulcasting') -- V. Svensson - Hyperlinks -- VI. GS Media - Hyperlinks -- VII. Filmspeler - Media Players -- VIII. Ziggo - Torrent Files -- IX. VCAST - Time Shifting -- X. Embedded Hyperlinks -- XI. Direct to Download Hyperlinks -- XII. Circumventing Access Restrictions -- XIII. Conclusion -- Conclusion -- I. The Recommendations -- II. Implications -- III. Final Comments.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Keywords: Copyright -- European Union countries; Freedom of expression -- European Union countries